ID 13 – Motor cortex connectivity in cervical dystonia: An fMRI study. Issue 3 (March 2016) - Filip, P.; Gallea, C.; Léhericy, S.; Bareš, M.
Abstract : Objective: To better understand motor cortex position in dystonia pathophysiology by its connectivity in normal population and cervical dystonia patients. Methods: Functional magnetic resonance imaging has been performed in 25 healthy controls and 25 patients (all right-handed) in a motor timing task requiring simple movement of right hand – key press – to intercept a moving target. Left side premotor cortex was used as the seed for the psychophysiologic interaction model, based on the area showing decreased activity in dystonia patients compared to the healthy controls. Results: Decreased connectivity to bilateral parietal cortex (mainly area 7) was found in cervical dystonia patients in comparison to the healthy controls. This difference is suggestive of lower associative information exchange in the disease, possibly leading to the lower behavioral performance in the task. Conclusions: Our results point to possible impairment of communication between premotor cortex and parietal associative areas in cervical dystonia patients. This notion is well in accord with the newly emerging dystonia definition as a multiple node network pathology involving basal ganglia, cerebellum and specific cortical areas. Key message: Our findings support the role of a complex pathways pathway disruption, even of multiple cortical information processing levels, in dystonia pathophysiology.